Methylprednisolone up-regulates annexin A1 (ANXA1) to inhibit the inflammation, apoptosis and oxidative stress of cigarette smoke extract (CSE)-induced bronchial epithelial cells, a chronic obstructive pulmonary disease in vitro model, through the formyl peptide receptor 2 (FPR2) receptors and the adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK) pathway. Issue 2 (1st February 2022) - Yu, Chan; Zhang, Linghui
ABSTRACT: Chronic obstructive pulmonary disease (COPD) is a progressive degenerative disease, of which smoking is the main causer. We carried out this study with the aim of exploring the underlying mechanism of methylprednisolone (MP) treating the COPD. To stimulate COPD in vitro, cigarette smoke extract (CSE)was employed to induce human bronchial epithelial cells BEAS-2B. With the help of MTT and Tunel assays, the viability and apoptosis of BEAS-2B cells after indicated treatment were assessed. The levels of inflammatory response and oxidative stress were determined by the changes of markers basing on their commercial kits. Additionally, annexin A1 (ANXA1) expressions at both protein and mRNA levels were assessed with Western blot and Reverse transcription‑quantitative PCR (RT-qPCR). Moreover, the expressions of apoptosis- and formyl peptide receptor 2 (FPR2) receptors and the adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK) pathway-related proteins were determined with Western blot., related proteins and proteins. As a result, MP up-regulated the ANXA1 expression in CSE-induced BEAS-2B cells. MP enhanced the viability but suppressed the apoptosis, inflammatory response and oxidative stress of CSE-induced BEAS-2B cells via regulating FPR2/AMPK pathway, while ANXA1 knockdown exhibited oppositive effects on them. In conclusion, MP up-regulated ANXA1 to inhibit the inflammation, apoptosis and oxidative stress of BEAS-2B cells induced by CSE, alleviating COPD through suppressing the FPR2/AMPK pathway.